Isolation And Identification of Biosurfic Producing Bacteria From Contact Pond Pond WWTP Sludge - Roy Astika Simatupang; M. Hasbi M. Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to obtain bio surfactant-producing bacteria originating from the IPAL pond sludge of the palm oil industry at PT. Eka Dura Indonesia, Ujung Batu, Rokan Hulu, Riau Province. This research uses the survey method. Sludge samples are taken from the Contact pond by using a sample bottle, then put into a cooler, and taken to the laboratory. Next, 5 grams of sludge sample was weighed and the dissolution of the sample was carried out using BPS (Buffer Phosphate Saline) media. Furthermore, this sample was enriched with BHI (Brain Heart Infusion) media, then incubated for 24 hours. Furthermore, this sample was diluted using 0.98% NaCl to 10-6 dilution, and counted the number of bacteria growing, using Petrifilm at 10-4, 10-5 and 10-6 dilution. Then the planting and purification of bacteria were carried out using Blood Agar and MacConkey Agar. Then, it was identified using biochemical tests and PCR (Polymerase Chain Reaction) tests. The results found 2 types of bacterial isolates with 2 species producing bio surfactants, Proteus mirabilis, and Enterobacter aerogenes. The DNA rank of the bacterial species that has the highest Emulsification Index, which is 100% Proteus mirabilis.Keywords: Oil contamination, Biochemical Test, PCR (Polymerase Chain Reaction) Test, Proteus mirabilis and Enterobacter aerogenes